CALCULATION OF CENTRAL JAVA PROVINCE REGION AREA USING SHOELACE FORMULA BASED ON THE GADM DATABASE - Setiawan, Adi; Sediyono, Eko; Mahatma, Tundjung (PATTIMURA UNIVERSITY, 2022)
This study proposes the use of the shoelace formula to determine the area of the regencies and towns/cities in the province of Central Java, which is based on the boundaries of the cities, regencies, (sub-) districts, and villages using the database from the GADM (Global Administrative Area). The results obtained are then compared with the Karney polygon method. With the shoelace formula, the area of Central Java province is 34365.40 km2 (4.77% wider than the reference area), while the Karney polygon method yields 34379.48 km2 (4.81% wider than the reference area). The area calculated using the boundaries of sub-districts is closer to the reference area if compared to using the boundaries of the regencies/cities and of villages. MdAPE values of 6.46 % and 6.54 % are obtained using the shoelace formula and the Karney polygon method respectively.